Peran Islamic Worldview dalam Membentuk Identitas dan Kepribadian Muslim Kontemporer - Khidir Mansyur; Sumiran Sumiran (TSAQOFAH, 2026)
The development of globalization, digitalization, and secularization presents complex challenges to the formation of contemporary Muslim identity and personality, particularly through shifts in value orientation, crises of meaning, moral relativism, and the penetration of global culture. This study aims to analyze the role of the Islamic worldview in shaping contemporary Muslim identity and personality based on the perspectives of Islamic philosophy and education. This study used a qualitative approach with a library research method. Data were collected through a critical review of the Qur’an, hadith, classical literature, and reputable scientific publications discussing the Islamic worldview, Muslim identity, Islamic education, and the development of modern society. The data were analyzed using content analysis techniques with a descriptive-analytical approach and conceptual synthesis. The results show that the Islamic worldview functions as an epistemological, ontological, and axiological paradigm that shapes Muslims’ ways of thinking, belief systems, moral orientation, and social behavior. The integration of the values of tawhid, trustworthiness, justice, ihsan, and responsibility forms a strong Islamic identity, a personality that is adaptive to change, and the ability to filter the influence of global culture without losing the principles of sharia. The conclusion of this study emphasizes that strengthening the Islamic worldview has a strategic role in building Muslim character that is characterized by integrity, moderation, productivity, and competitiveness in the contemporary era. The implications of this study provide a conceptual foundation for the development of Islamic education curricula, character formation, and the formulation of educational policies oriented toward strengthening Islamic identity amid global dynamics.